Partisipasi Masyarakat Lokal Medan: Sebuah Tinjauan Atas Kriteria Nasional Pada Proses Penetapan Sebagai Cagar Budaya - Isnen Fitri (Balai Arkeologi Sumatera Utara, 2015)
Among the important problems encountered in the implementation of cultural heritage preservation in Indonesia nowadays is the establishment of the cultural register in national, province, or regency/city levels. Criteria in article 5 of the Law on Items of Cultural Heritage No.11/2010 are insufficient for the process of assigning historical assets as cultural heritage items. The criteria also seem to merely be a “copy and paste” of the previous law. Meanwhile, at the global level, during the last several decades, many countries have begun to adopt the concept of the important values of heritages, which is depicted in the Burra Charter as a reference to develop criteria in assigning items of cultural heritages. To improve our national criteria in the near future, this study is aimed at evaluating national criteria in article 5 based on opinions of 33 representatives of local communities in Medan, as stakeholders in the preservation of cultural heritages in the city of Medan, by performing interviews and group discussions using Nominal Group Technique or NGT. From the diverse opinions of the 33 participants obtained from the two phases of data collecting process, it is concluded that our national criteria in assigning an item of cultural heritage that were mentioned in article 5 of the Law on Items of Cultural Heritage No.11/2010 are still obscure, difficult to measure, overlapping, and not quite in line with global trend. Most participants disagree that age is used as the main criteria. There are a number of suggestions (inputs) from the participants to improve the sentences in article 5 to form criteria that are easier to measure and independent.